RHEGMATOGENOUS RETINAL DETACHMENT SURGERY - A REVIEW - Ferreira, Nuno Pinto (2017)
Rhegmatogenous retinal detachment (RRD) remains a major cause of emergency assistance in our ophthalmology departments. We struggle for the improvement of visual outcome of our patients after RRD surgery by trying to optimize our surgical methods and techniques. The decision of which surgical procedure to use in the treatment of RRD still depends on a variety of factors and surgeon’s preference. Until date there was only one major randomized clinical trial that drew some guidelines for our clinical practice. This present work has the main purpose of reviewing the major articles published so far on RRD surgery with the goal of creating a rational for our day practice for the best functional and anatomic results. Although many variables are involved in RRD treatment, prospective, multicentric, randomized studies are needed.